PARTICIPATORY MANAGEMENT TO PROMOTE THE PERFORMANCE OF TEACHERS IN EDUCATIONAL INSTITUTIONS UNDER THE BANG KHUN THIAN DISTRICT OFFICE NETWORK 71 BANGKOK - Rimkhet, Pensakao; Kettanom, Thasporn (Journal of MCU Nakhondhat, 2025)
The objective of this research was to study the level and methods of developing participatory administration to promote the performance of teachers in educational institutions. Under the Bang Khun Thian District Office, Network 71, Bangkok. Descriptive research methods the sample group includes teachers in educational institutions. Under the Bang Khun Thian District Office, Network 71, 144 people by simple randomization using a lottery method. The tool used was a questionnaire. It has the characteristics of a 5 - level evaluation scale and an interview from. It has a consistency index ranging from 0.67-1.00 with a confidence value of 0.84. Statistics used include percentages, means, standard deviations and content analysis. The research results found that Participatory management to promote teachers’ performance Overall it is at a high level. When considering each aspect, it was found that it was at a high level in every aspect. Ordered by average from highest to lowest as follows: Setting common goals and objectives in terms of independence and responsibility in work. The aspect of mutual trust and the aspect of commitment. There were development guidelines as follows: 1) Setting common goals and objectives you should set clear goals. Communicate to team members together, including planning and defining responsibilities. 2) Independence regarding work responsibilities teachers can choose the steps. How to work and make decisions in assigned tasks independently. 3) Trust aspect administrators believe in teachers’ knowledge and abilities, which makes teachers want to do good and valuable things for those who trust them. 4) Commitment aspect administrators and teachers interact positively and work together as one. Work with intention willingness and teachers should participate in decision-making in operations, making them feel part of the educational institution.